2007
DOI: 10.3174/ajnr.a0871
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Age and Symptom Status on Silent Ischemic Lesions after Carotid Stenting with and without the Use of Distal Filter Devices

Abstract: BACKGROUND AND PURPOSE:The routine use of distal filter devices during carotid angioplasty and stent placement (CAS) is controversial. The aim of this study was to analyze their effects on the incidence of new diffusion-weighted imaging (DWI) lesions as surrogate markers for stroke in important subgroups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…The overall results and various subgroup analyses of this series have been reported previously [6,9,10]. …”
Section: Patient Populationmentioning
confidence: 80%
See 1 more Smart Citation
“…The overall results and various subgroup analyses of this series have been reported previously [6,9,10]. …”
Section: Patient Populationmentioning
confidence: 80%
“…Using this imaging modality and the data of our prospective registry, we had recently analyzed the impact of cerebral protection devices, as well as the influence of advanced age on the incidence of new brain lesions after CAS [6,9,10]. The aims of this study were to determine angiographic and clinical risk factors for new DWI lesions after CAS in a first step and to subsequently generate a simple risk score by combining independent risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…However, these series compare protected series with historical controls which encompass considerable variation in presenting symptoms and age and overlook important technical advances such as dedicated carotid stents, fine guidewire technology, improvements in periprocedural pharmacological support and, of course, learning curve [2,3]. Kastrup et al [22] demonstrated that age and symptom status influenced the incidence of lesions on DWI following CAS.…”
Section: Discussionmentioning
confidence: 99%
“…3,18–21) Theoretically, due to its larger pore size, the Spider FX may have a lower capture efficiency and may elicit more embolic complications than other eccentric filter EPDs. 22) The different capacity of each filter may also affect distal debris migration between the filter and vessel wall.…”
Section: Discussionmentioning
confidence: 99%